Scoping Study Report: Potential Existing Value Chains in the North-West Region of Tunisia - Dhehibi, Boubaker; Souissi, Asma; Frija, Aymen; Ouerghemmi, Hassen; Alary, Veronique; Idoudi, Zied; Rudiger, Udo; Rekik, Mourad; Dhraief, Mohamed Zied; Oueslati-Zlaoui, Meriem; Majri, Rihab; Ouji, Mourad (International Center for Agricultural Research in the Dry Areas, 2023)
The objective of this report is to select the main value chains with potential to integrate the agroecological principles in the Northwest of Tunisia. A descriptive analysis on the two governorates chosen was first made, then 4 focus group discussions were organized with local farmers associations. The VC assessment according to agroecological principles conducted with the main actors places the olive oil VC as the major value chain with agroecological character.